Evaluation of Sour Gas Field Development Strategy: A Feasibility Study in Indonesia using PSC Gross Split Mechanism - Praditya, Yusuf Alfyan; Dalimunthe, Gallang Perdhana; Prawiraatmadja, Widhyawan (International Journal of Economics Development Research (IJEDR), 2025)
PetroComp, a private oil and gas operator in Eastern Indonesia, has a limited room for gas production growth. A potential new long-term gas sales agreement (GSA) with PT. SMC, could double PetroComp’s gas production and address its long-term growth needs. Jala field is the potential undeveloped resource to fulfill the gas demand requirement, however it contains high CO2 concentration which presents substantial investments for its development. Three development scenarios of Jala field are evaluated in the study, including a potential integration of CCUS.This study aims to evaluate the economic feasibility of the three development scenarios of Jala sour gas field using a Discounted Cash Flow (DCF) method to determine the best development strategy for PetroComp and Government of Indonesia. Conventional onshore development approach provides the highest NPV at US$ 113.8 million, meanwhile CCUS and full offshore development scenarios are not economic due to its high investment cost. Gas production volume and gas price are the most sensitive parameters affecting the project’s profitability based on the sensitivity analysis. Uncertainty analysis suggests a promising thick positive NPV is expected from the project with the P90-P50-P10 cases are ranging from US$ 50.8 – 173.9 million. Time-dependent evaluation concludes the impact on profitability start to de-escalate exponentially if the project is delayed for more than four years (>10% NPV impact) at the given PSC period until 2045. This study is intended to support evidence-based decision-making by PetroComp in developing the high-CO2 Jala gas field and advancing the company’s long-term growth strategy.